2023
DOI: 10.1021/acscatal.3c00651
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Identification for Glycerol Hydrodeoxygenation over the Oxygen Modified Molybdenum Carbide Surface

Abstract: Density functional theory and microkinetic reactor modeling were used to investigate the hydrodeoxygenation (HDO) mechanism of glycerol on the oxygenated Mo2C catalyst surface to understand the activity and product selectivity under practically relevant reaction conditions. Reactor simulations with multiple active site models predicted that a fully oxygenated surface with acid–base (OH,O) pairs is active for glycerol dehydration and it can selectively cleave one C–O bond to produce 3-hydroxypropanal (HPA). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Clearly, the hydrolysis rate is markedly proportional to the amount of Brønsted acid. This phenomenon is consistent with a previous study that reported oxygen-modified Mo 2 C can facilitate the dehydration of glycerol to 3-hydroxypropanal under an H 2 atmosphere . Therefore, the H + –H – pair plays bifunctional roles as the hydrogenation site for the DPE hydrogenation step and the acidic site for the CHEPE hydrolysis step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the hydrolysis rate is markedly proportional to the amount of Brønsted acid. This phenomenon is consistent with a previous study that reported oxygen-modified Mo 2 C can facilitate the dehydration of glycerol to 3-hydroxypropanal under an H 2 atmosphere . Therefore, the H + –H – pair plays bifunctional roles as the hydrogenation site for the DPE hydrogenation step and the acidic site for the CHEPE hydrolysis step.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is consistent with a previous study that reported oxygenmodified Mo 2 C can facilitate the dehydration of glycerol to 3hydroxypropanal under an H 2 atmosphere. 58 Therefore, the H + −H − pair plays bifunctional roles as the hydrogenation site for the DPE hydrogenation step and the acidic site for the CHEPE hydrolysis step. By tuning the O content of Mo 2 TiC 2 , we could modify the hydrogenation-acid catalysis balance by adjusting by the hydrogen spillover mechanism.…”
Section: Acsmentioning
confidence: 99%